Revision of the coral reef crab genus Tweedieia Ward, 1935 (Decapoda: Brachyura: Xanthidae). Issue 1 (12th January 2022) - Lasley, Robert M; Smith, Austin; Paulay, Gustav; Ng, Peter K L
Abstract: Xanthid crabs of the genus Tweedieia Ward, 1935, are among the most beautiful decapod cryptofauna in Indo-West Pacific coral reefs, with an ornate arrangement of granules and setae, in combination with an eye-catching color pattern. The genus and three recognised species ( T. odhneri (Gordon, 1934 ), T. laysani (Rathbun, 1906 ), and T. brevidactyla Dai & Yang, 1998 ) are revised, and new diagnoses and figures are provided. The COI barcoding gene of 38 specimens was sequenced and used to generate maximum likelihood and neighbor-joining trees. Tweeedieia brevidactyla is here synonymized with T. odhneri . Tweedieia now comprises only two species, differentiated by morphological characters and sequence data. Tweedieia odhneri ranges from the western Indian Ocean to the Hawaiian Islands and French Polynesia, while the rare T. laysani is only recorded from the Hawaiian Islands. These crabs appear to favor clear, oligotrophic, oceanic waters and are common on oceanic islands and rare around continents and large islands of Australasia.